Development of A Game-Based Pencak Silat Learning Model for Students in Elementary School - Devina Aristia; Ipang Setiawan (Journal of Physical Education Health and Sport, 2026)
Learning game functions as a strategy that provides a learning experience that is natural and relevant to real-life situations, therefore able to relate learning materials to daily experiences for students. This research aims to produce a game-based learning model on pencak silat martial arts materials for elementary school grade V students that can be applied in small and large groups in Margoyoso District, Pati Regency. This research applies  a Research and Development (R&D) approach that aims to produce and validate learning products in the form of a "Pencak Silat Learning Through Games" model for elementary school students. The population in this study consisted of students in the elementary school class of Margoyoso District, with a sample of 15 students in a small-scale pilot study and 60 students in a large-scale study taken from three public elementary schools. The data analysis technique used is quantitative descriptive analysis, which includes calculating the percentage of results from expert validation, questionnaires, and observation sheets. The results of the study showed that the learning model of pencak silat through the developed game obtained "very good" based on expert evaluation and test results with students. Thus, this learning model is considered feasible to be used to improve basic pencak silat activities and skills among elementary school students. The conclusion that the existence of a pencak silat learning model through games can overcome the problem of limited facilities and infrastructure, including open areas, needs to be done to support the effectiveness and smooth learning process.